LOWBALLING PRACTICE AND QUALITY OF FINANCIAL REPORTING IN NIGERIA. - Agbaje, wale henry (Universitas Kuningan, 2024)
There are still issues facing financial reporting and this causes an inability to achieve a high-quality financial report and this remain one of the interest of regulators and practitioners. Specifically, the study examines the impact of lowballing pricing on relevance of financial reporting quality, faithfulness of financial reporting quality and timeliness of financial reporting quality. The survey research design was employed in this work. Primary source of data was used for empirical analysis. The population of this study include 667staff and management of banks operating in Akure, Ondo State with a sample size of two-hundred and fifty (250). Strictly structured questionnaire was administered to two-hundred and fifty staff of banks in Akure out of which two-hundred and eleven was returned. The demographic information was analyzed with the aid of frequency distribution and presented via a pie chart with the aid of SPSS. The study utilized ordinary least square regression to examine the relationship between lowballing pricing and quality of financial report with the aid of E-views. The result revealed a significant relationship between lowballing pricing and relevance of financial report (t = 3.0070, p<0.05); insignificant relationship between lowballing pricing and faithfulness of financial report (t = 0.0800, p> 0.05) and a significant effect between lowballing pricing and timeliness of financial report (t = 2.8754, p<0.05). The study concludes that lowballing pricing has a significant effect on the quality of financial report in Nigeria. It is therefore recommended that banks should carefully evaluate the decision on lowball audit fees and weighing the potential cost savings against the potential risks to financial reporting quality. The cost savings from lowballing fees may be offset by the cost of compromised audit quality, which could result in increased regulatory scrutiny, financial restatements and reputational damage. Keywords: lowballing pricing, faithfulness, relevance, timeliness of financial reporting